268 Smart polymer implants as an emerging technology for treating airway collapse in OSA: a proof of concept study. (3rd May 2021) - Sideris, Anders; Wallace, Gordon; Lam, Matthew; Kitipornchai, Leon; Lewis, Richard; Jones, Andrew; Jeiranikhameneh, Ali; Hingley, Lachlan; Beirne, Stephen; Mackay, Stuart G
Abstract: Introduction: Implantable 3D printed 'smart' polymers are an emerging technology with potential applications in treating collapse in adult obstructive sleep apnea through mechanical airway manipulation. There is a paucity of devices that are commercially available or in research and development stage. Limited studies have investigated the use of implantable smart polymers in reversing the collapsibility of the pharyngeal airway by creating counter forces during sleep. This paper describes an application of implantable magnetic polymer technology in an in-vivo porcine model. Study Objectives: To assess the use of a novel magnetic polymer implant in reversing airway collapse and identifying potential anatomical targets for airway implant surgery in an in-vivo porcine model. Methods: Target sites of airway collapse were genioglossus muscle, hyoid bone and middle constrictor. Magnetic polymer implants were sutured to these sites and external magnetic forces, through magnets with pull forces rated at 102kg and 294kg, were applied at the skin. The resultant airway movement was assessed via nasendoscopy. Pharyngeal plexus branches to the middle constrictor muscle were stimulated at 0.5mA, 1.0mA and 2.0mA and airway movement assessed via nasendoscopy. Results: At the genioglossus muscles large magnetic forces were required to produce airway movement. At the hyoid bone, anterior movement of the airway was noted when using a 294kg rated magnet. At the middle constrictor muscle, an anterolateral (or rotatory) pattern of airway movement was noted when using the same magnet. Stimulation of pharyngeal plexus branches to the middle constrictor revealed contraction and increasing rigidity of the lateral walls of the airway as stimulation amplitude increased. The resultant effect was prevention of collapse, a previously unidentified pattern of airway movement. Conclusion: Surgically implanted smart polymers are an emerging technology showing promise in the treatment of airway collapse in obstructive sleep apnea. Future research should investigate their biomechanical role as an adjunct to treatment of airway collapse through nerve stimulation. Support (if any): Garnett-Passe and Rodney Williams Memorial Foundation, Conjoint Grant, 2016-18.